1988
DOI: 10.1002/masy.19880130123
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of cationic alkene polymerization

Abstract: In recent years progress has been made in mathematical modelling of complicated chemical systems. Simulation of reactions with computational techniques offers an excellent method for testing the extent to which a reaction mechanism is indeed understood. After considering the principles of modelling and its advantages in general we present a new type of modelling of polymerizations and its advantages in particular. This method typically involves time‐stepwise integration of kinetic equations and works at a leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In accordance with literature reports, we have not been able to detect compound P1 in the BCl 3 -initiated reaction of cumyl chloride 1 with isobutylene, even when only 1 equiv of isobutylene was slowly added to a mixture of 1 and BCl 3 in CH 2 Cl 2 . The polymerization of isobutylene could be suppressed, however, when BnEt 3 N + BCl 4 - was present in the reaction mixture, and under otherwise identical conditions, the selective formation of the 1:1-product P1 was observed, even when an excess of isobutylene was present (Scheme ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with literature reports, we have not been able to detect compound P1 in the BCl 3 -initiated reaction of cumyl chloride 1 with isobutylene, even when only 1 equiv of isobutylene was slowly added to a mixture of 1 and BCl 3 in CH 2 Cl 2 . The polymerization of isobutylene could be suppressed, however, when BnEt 3 N + BCl 4 - was present in the reaction mixture, and under otherwise identical conditions, the selective formation of the 1:1-product P1 was observed, even when an excess of isobutylene was present (Scheme ).…”
Section: Resultssupporting
confidence: 93%
“…The formation of telechelic polymers by cumyl chloride 1 (1-chloro-1-methyl-ethyl)benzene/BCl 3 -initiated polymerizations of isobutylene has first been reported by Kennedy and Nuyken (Inifer mechanism). The analogous process using biscumyl chloride, 2 , and triscumyl chloride, 3 , led to the formation of bi- and trifunctional polymers. While these polymerizations were not living under the original reaction conditions, slight modifications led to living systems. ,
…”
Section: Introductionmentioning
confidence: 98%
“…We have addressed this problem by comparing the reactivities of persistent low molecular weight carbocations with those of higher molecular weight homologues. Our approach thus differs from related earlier work, which has been based on apparent propagation rate constants. , …”
Section: Introductionmentioning
confidence: 75%
“…On the basis of pioneering studies of Kennedy and co-workers in the early 1980s, the living polymerization of isobutylene has become an active field of research. Whereas the treatment of isobutylene with Brönsted acids, Lewis acids, and Lewis acid/alkyl halide mixtures in nonnucleophilic solvents yielded polymers with broad molecular weight distribution, the addition of Lewis bases as amines, amides, sulfides, esters, etc., has been found to reduce the polydispersity of the polymer. , Mixtures of alkyl halides, Lewis acids, and tetraalkylammonium halides, which are characterized by well-defined Lewis acid/base coordination equilibria, have also been found to be efficient initiators for living isobutylene polymerization. In previous investigations on the Lewis acid promoted reactions of alkyl halides with alkenes, we have shown that the information derived from low molecular weight compounds provides valuable information on the rates of initiation, propagation, and transfer steps in carbocationic polymerization. ,, We have now extended this method for studying some aspects of the living carbocationic polymerization of isobutylene by investigating the initial steps of these reactions where the individual oligomers can be detected separately. Because of the backstrain-enhanced ionization rates of diisobutylene hydrochloride ( 1 ) and triisobutylene hydrochloride ( 2 ), these compounds are more efficient initiators for carbocationic polymerization than tert- butyl chloride. ,, ,,,,,,, We have, therefore, used 1 and 2 in combination with boron trichlori...…”
Section: Introductionmentioning
confidence: 99%